Gaucher Disease: A Comprehensive Review - Mokhtar Abdullah Alkhalaf et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Gaucher disease (GD) is a rare lysosomal storage disorder caused by mutations in the GBA1 gene, which encodes the enzyme glucocerebrosidase. This deficiency results in the accumulation of glucocerebroside in macrophages, leading to multi-organ involvement. GD manifests in three main types, each with distinct clinical features. Recent advancements in enzyme replacement therapy (ERT), substrate reduction therapy (SRT), and novel treatment strategies such as gene therapy have improved patient outcomes significantly. This review explores the pathophysiology, clinical manifestations, diagnostic approaches, treatment modalities, and future prospects for managing Gaucher disease. Received Date: November 05, 2024 Accepted Date: November 26, 2024 Published Date: December 01, 2024 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/260 https://doi.org/10.5281/zenodo.14260224